AN LEANING POEM ON THE EARTH TIME: MYTH AND TRACES OF NARRATION IN BEHCET NECATIGIL - Fatih ARSLAN (Fırat University, 2019)
At the very beginning of what the world has in itself, there are undoubtedly myths, stories, archetypes of human souls. The person who started by fearing the meaning of the earth has developed the ways of relieving himself. Exploring the world first, then, is very important in the adventure of maturity. Despite all forms of innovation, the pursuit of mythic values is a difficult situation to explain. The common values of man, the common unconscious sense of the person repeatedly points to the mite. Though in different names and forms, myth brings a liberty to man's word. The accumulation of many years is the source of all cultures. The approximate values of a living, thinking, producing person are best defined by their mythic material.Turkish poetry tradition has used mythology in different time periods and in different forms. This closeness, which started in the form of translations in the early periods, became more functional especially in poetry. The Behçet Necatigil poem, one of the strong consciousness of the Republican poetry, frequently used different reflections of mythology. The poet, who mainly embraced Greek mythology, made an important contribution to the image burden. Necatigil, which has a wide cultural background, has benefited from many materials from Turkish mythology, Western mythology and religious culture sources and used it in its own poetic world in universal forms. The most important point that draws attention here is the intention to reach common structure as we tried to mention above. The mythic universal structure is combined with the poet's intention to universalize. In a sense, Necatigil has used these universal forms in the intention of poetry world poetry.